Textile elements for car seat to improve user's driving comfort. (October 2021) - Warska, Michalina; Barburski, Marcin; van Langenhove, Lieva
The main motive for this research is the desire for the improvement of the automotive seat occupant's comfort by designing a heating mat prototype made with distance knitting technology with heating elements. In this study, the following design steps were undertaken: preparation of the trajectories of heating cables, calculating the resistance needed to obtain the estimated power of the whole mat, testing of available electroconductive yarns to assign the most suitable yarn to a specific design, preparation and testing of five heating mat prototypes with three various trajectories of the heating element. All samples were evaluated with the same criteria in order to find the most promising design. After all experiments, a prototype with stainless-steel Bekaert® VN 12.2 coated yarn as a heating element, showed the best performance, especially in combination with distance knitted fabric thanks to its internal construction. This work demonstrates that a three-dimensional distance knitted fabric with a heating element introduced into its structure will ensure the physiological sitting comfort. After further subsequent studies, the proposed method can be adapted for industrialisation by using warp knitting machines, thus improving the quality and durability of the heating mat.